Morphological and molecular identification of Fusarium spp. isolated from maize kernels in Java and Lombok, Indonesia - Ani Widiastuti; Monica Lucky Karlina; Kurnia Ritma Dhanti; Yufita Dwi Chinta; Tri Joko; Suryanti; Arif Wibowo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Widiastuti A, Karlina ML, Dhanti KR, Chinta YD, Joko T, Suryanti, Wibowo A. 2020. Morphological and molecular identification of Fusarium spp. isolated from maize kernels in Java and Lombok, Indonesia. Biodiversitas 21: 2741-2750. Fungal contamination of maize is a serious problem in Indonesia. Fusarium spp. infect maize in the field will be continuing to contaminate in the post-harvest period even though disease symptoms are not always emerged. Some Fusarium spp. produced mycotoxins which are harmful to human and animal health. Aims of this research were to reveal the presence of Fusarium spp. from both symptomatic and unsymptomatic maize, and to identify them based on morphological characteristics and molecular analysis. Samples of maize were collected from maize cultivation areas in East Java (EJ), Central Java (CJ), West Java (WJ), Yogyakarta Special Province (DIY), and Lombok, West Nusa Tenggara. Fusarium spp. were isolated in a single spore method and cultured in potato dextrose agar (PDA) medium for morphological identification of macro-and microconidia. Molecular identification was conducted by PCR assay using species-specific primers. Furthermore, unidentified species were analyzed by DNA sequence. This research found four species of mycotoxigenic Fusarium isolated from maize-based on molecular identification, which were Fusarium verticillioides (15 isolates), F. proliferatum (6 isolates), F. graminearum (1 isolate) and F. asiaticum (1 isolate). This research showed a novel report of F. asiaticum infection on maize kernel in Indonesia.